Facts about Copper - Linda B. Bobroff (EDIS)
Revised! FCS-8804, a 3-page fact sheet by Linda B. Bobroff, answers questions about copper, why we need it, what happens if we don’t get enough, how much we need, how we can get enough and not too much. Includes references. Published by the UF Department of Family Youth and Community Sciences, June 2008.